Study on Feeding Supplements for Cattle Fattening on Smallhoder Fammers in paek District Xiengkhouang Province - NAOYENG , Khamkeo; LORBLIAYAO, Viengsouk (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
This study was investigated on growth performance of Local Yellow Cattle and was used 90 days. The experiment was done at ToneNeuan and Khong Village, Peak District and XiengKuang Province. The objective was evaluate growth rate and economic return. The experimental design was used T-Test there were 2 groups, each group there were 10 heads. Each group were used fresh grasses (Nepeir, Ruzi, Guatemala and natural grass) feed was given of 15% on Live weight gain on fresh basic, but in the second group was supplemented with (corn 50% + rice bran 30% and soybean meal 20%) and was given 1kg/head/day and supplemented with mineral box. Animal was used initial live weight of 220.75kg and 3 years of ages. Water was supply ad libitum. The result were show that: Live weight gain of second group was increased and higher than first group as non-supplementation, and supplemented with soybean waste were significantly higher (P<0.05) ADG of second group of 708g/day. And first group of 233g/day. From this studies on growth performance of Local Yellow Cattle, the growth rate of Cattle were supplemented with corn, rice bran and soybean meal plus mineral box was higher than non-supplementation. Second group as supplementation feed was high input than first group as non-supplementation, but economic return was lower than second group.